Biological variation: recent development and future challenges - Sandberg, Sverre; Carobene, Anna; Bartlett, Bill; Coskun, Abdurrahman; Fernandez-Calle, Pilar; Jonker, Niels; Diaz-Garzon, Jorge; Aarsand, Aasne K. (WALTER DE GRUYTER GMBH, 2022)
Biological variation (BV) data have many applications in laboratory medicine. However, these depend on the availability of relevant and robust BV data fit for purpose. BV data can be obtained through different study designs, both by experimental studies and studies utilizing previously analysed routine results derived from laboratory databases. The different BV applications include using BV data for setting analytical performance specifications, to calculate reference change values, to define the index of individuality and to establish personalized reference intervals. In this review, major achievements in the area of BV from last decade will be presented and discussed. These range from new models and approaches to derive BV data, the delivery of high-quality BV data by the highly powered European Biological Variation Study (EuBIVAS), the Biological Variation Data Critical Appraisal Checklist (BIVAC) and other standards for deriving and reporting BV data, the EFLM Biological Variation Database and new applications of BV data including personalized reference intervals and measurement uncertainty.
Keywords: biological variation; BIVAC; EuBIVAS; personalized reference intervals (prRI); reference change value